STRATEGI MENINGKATKAN KEPATUHAN STANDAR PELAYANAN PUBLIK (Studi Kasus Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Riau) - Akhmad Fadillah; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The achievement of Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Provinsi Riau in improving the compliance of public service standards is inseparable from several special points which include the value of administrative documents, electronic and non-electronic facilities and infrastructure and facilities, and adequate human resources in carrying out public services. However, the availability of non-electronic public service information (booklets, pamphlets, etc.) is still focused or in the DPMPTSP office, and inadequate facilities and infrastructure of special needs, infrastructure for people with physical disabilities (eg wheelchairs, guiding lanes, special toilets ) and breastfeeding room.In this study, the concept of theory used is the strategy theory proposed Ellitan (2008) as a research instrument, where to measure the strategies applied to an organization or company include; technology strategy, innovation strategy, and operation strategy. This research uses qualitative descriptive method with data collection techniques including interview, observation and documentation study.The results showed that the strategy applied DPMPTSP Riau Province to run optimally. This is evidenced by the presence of human resources / service providers in providing services, service systems and availability of information electronically and non-electronically, online licensing innovation, service provision availability, online complaint management, performance appraisal of service users through Community Satisfaction Survey SKM/ e-voting, and questionnaire), as indicator of compliance standards established by Ombudsman RI. The strategy adopted by DPMPTSP of Riau Province has benefited the service user's certainty and convenience, but there are some weaknesses in the indicator in service for users with special needs services that are not fully supported by special needs (such as special needs, wheelchair and so on ), as well as the form of direct socialization in encouraging the public in the field of licensing services and non-licensing.Keywords: Public Service, Service Strategy, Technology Strategy, Innovation Strategy, and Operation Strategy.